Resubmission of the adjustment unit price for VO #09 prefabricated steel structure with grade alternation from S355J0 to S355ML & S460ML - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding resubmission of the adjustment unit price for VO #09 prefabricated steel structure with grade alternation from S355J0 to S355ML & S460ML of BRAC University new campus project.